ANALISIS PENTINGNYA PENDAFTARAN HAK MEREK DAGANG BAGI UMKM - Ardila, Revi; Fitriyanti, Fadia (LPPM Universitas Bina Bangsa, 2025)
Usaha Mikro Kecil dan Menengah (UMKM) are trade and/or service sectors that must be protected by the state. Indonesia as a country of law is obliged to fulfill all the rights of its citizens, including legal rights. The legal protection provided by the state to the intellectual property of UMKM includes trademarks, patents, copyrights, industrial designs, trade secrets, the basis of integrated circuit layouts, and geographical indications. To get legal protection for the trademark used by UMKM, UMKM must immediately register the trademark with the Ministry of Law and Human Rights. By registering a brand, UMKM can get benefit, but there are still many UMKM who do not register it for various reasons. The research uses normative juridical research methods, literature data collection, qualitative analyst techniques, and descriptive writing techniques.